Canine small clear cell/T‐zone lymphoma: clinical presentation and outcome in a retrospective case series. (3rd June 2015) - Martini, V.; Marconato, L.; Poggi, A.; Riondato, F.; Aresu, L.; Cozzi, M.; Comazzi, S.
Abstract: Published studies, taken together, suggest the existence of a single canine lymphoma entity, with a small clear cell appearance by cytological evaluation, a histopathological T‐zone pattern and an aberrant CD45‐negative T‐cell phenotype, mostly characterized by long‐term survival. We describe clinical presentation and outcome in a retrospective case series of canine small clear cell/T‐zone lymphoma. Despite the reported predisposition of Golden retriever, this breed was not represented in our case series. Most dogs presented with stage V disease, whereas only few had clinical signs or peripheral cytopenias. Blood was almost always more infiltrated than bone marrow. Median survival confirmed the favourable prognosis described in literature, but a few dogs died within a short time. Also, a subgroup of dogs developed second malignancies, eventually leading to death. We did not investigate possible prognostic factors because of the wide variety in treatments, and further studies are needed to identify high‐risk animals.